147 The development of three-dimensional platform for patient-derived ovarian cancer tissue remodelling. A systematic literature review. (13th November 2020) - Sevinyan, L; Velliou, E; Gupta, P; Madhuri, K
Abstract : Introduction: There is an unmet requirement for ex vivo tumour models that would predict drug responses and in turn help determine treatment regimens and possibly predict resistance before clinical studies. Research has shown that three-dimensional models of ovarian cancer are more realistic than two-dimensional in vitro systems as they can capture patient in vivo conditions more accurately. Most of studies aiming to recapitulate the ovarian tumour characteristics and study chemotherapy responses use ovarian cancer cell lines. However, despite the advantages of utilising cancer cell lines, they are not as informative as systems applying patient derived cells. In this review we discussed the most recent advances in the creation of 3D ovarian cancer model that have used patient derived material, the challenges to overcome and future applications. Methods: Thorough systematic literature search was performed using electronic databases of MEDLINE, EMBASE and COCHRANE by 2 reviewers to identify relevant studies. The studies included in the current review met certain strict criteria. Results: 18 full papers and 11 conference abstracts were included in the review. We found that the vast majority of the 3D in vitro models developed for ovarian cancer studies are spheroid and hydrogel type models, both of which have their advantages, however do have significant limitations. Conclusion: This systematic review will provide a narrative synthesis of the platforms and methods used for three-dimensional models creation utilising patient-derived ovarian cancer material and their scientific and clinical application. We are currently exploring scaffold models to grow ovarian cancer cells ex vivo in order to personalise treatment.